2005
DOI: 10.1093/ajcn/81.3.578
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and risk of atrial fibrillation or flutter: the Danish Diet, Cancer, and Health Study

Abstract: Consumption of caffeine was not associated with risk of atrial fibrillation or flutter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
2
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 20 publications
2
72
2
9
Order By: Relevance
“…Prospective studies have not found significant associations between coffee consumption and the risk of coronary heart disease [24,25]. Contrary to public belief, caffeine intake of 500-600 mg daily does not increase the risk, frequency, or severity of cardiac arrhythmias [26,27]. Indeed, there is a growing list of age-related diseases wherein habitual caffeine intake of 400-600 mg (4-6 cups of coffee) daily reduces the risk.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies have not found significant associations between coffee consumption and the risk of coronary heart disease [24,25]. Contrary to public belief, caffeine intake of 500-600 mg daily does not increase the risk, frequency, or severity of cardiac arrhythmias [26,27]. Indeed, there is a growing list of age-related diseases wherein habitual caffeine intake of 400-600 mg (4-6 cups of coffee) daily reduces the risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of LCCs to open in response to much lower caffeine concentrations (e.g., 200 M) is pathophysiologically relevant. Heavy coffee drinkers can ingest an average of 1,000 mg of caffeine daily (14), which can bring their serum caffeine concentration close to toxic levels [Ͼ129 M (24)]. Such a toxic level can also be reached when someone accidentally uses an excessive amount of caffeine-containing substances (3).…”
Section: Effect Of Opening Caffeine-activated Lccsmentioning
confidence: 99%
“…Previous studies have pointed out that caffeine overdose causes various kinds of arrhythmias, [1][2][3] including atrial tachycardia. 4) Josephson, et al 4) reported a case of paroxysmal atrial tachycardia in a 42-year-old man with asymptomatic aortic regurgitation, after increased amounts of coffee consumption (30 cups a day) in addition to tea and cola.…”
Section: Discussionmentioning
confidence: 99%